2008
DOI: 10.1080/13504850600721965
|View full text |Cite
|
Sign up to set email alerts
|

Short-run macroeconomic determinants of remittances to Jamaica: a time varying parameter approach

Abstract: This article uses a time varying parameter model (TVP) to examine the macroeconomic determinants of cash remittances to Jamaica over the period January 1983 to April 2001. We anticipated a positive relationship between changes in remittances and foreign income. We find an investment component in the relationship between changes in remittances and domestic income. In addition, the relationship between changes in remittances, the unofficial exchange rate premium and the exchange rate differential are in line wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…Some researchers find evidence that remittances respond to favourable investment opportunities in the home country. These studies have used the interest rate of the home country or interest rate differential between the home and host country in their empirical models (Faini, ; Jackman, ; Cooray and Mallick, ; El‐Sakka and McNabb, ; Aydas et al., ; Allyene et al., ; Chami et al., 2005) as a test for the exchange or self‐interest theory of remittances. In particular, a positive coefficient on the interest rate or interest rate differential is regarded as an evidence of opportunistic remittances whereas an insignificant or negative coefficient would tend to invalidate support for remittances responding to favourable investment climate in the home country.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers find evidence that remittances respond to favourable investment opportunities in the home country. These studies have used the interest rate of the home country or interest rate differential between the home and host country in their empirical models (Faini, ; Jackman, ; Cooray and Mallick, ; El‐Sakka and McNabb, ; Aydas et al., ; Allyene et al., ; Chami et al., 2005) as a test for the exchange or self‐interest theory of remittances. In particular, a positive coefficient on the interest rate or interest rate differential is regarded as an evidence of opportunistic remittances whereas an insignificant or negative coefficient would tend to invalidate support for remittances responding to favourable investment climate in the home country.…”
Section: Introductionmentioning
confidence: 99%
“…Motivated by the large inflows of migrant remittances (15% of GDP on average), there is an ongoing debate in Jamaica whether members of the diaspora should have an elected representative in the House of Parliament (Alleyne et al, 2008). In Jamaica the two major political parties also compete for the financial backing of the diaspora community.…”
Section: Introductionmentioning
confidence: 99%
“…Besides economic activities, researchers explored other macro indicators as potential influencers of remittance outflows, which significantly improved the understanding of the sources of remittances volatility. Among these indicators is the interest rate and return on investment (or, in some studies, the interest rate differential between the host and home countries), which capture the investment motive and thus play a role in migrants' decisions to invest in the host or home country (El-Sakka and McNabb 1999;Aydas, Neyapti, and Metin-Ozcan 2005;Alleyne, Kirton, and McLeod 2008). Moreover, other studies have investigated the role of the exchange rate and (most of them) found that a depreciation in the home country's exchange rate has a positive impact on remittance outflows, as more funds can be transferred at low exchange rates (Higgins, Hysenbegasi, and Pozo 2004).…”
Section: Literature Reviewmentioning
confidence: 99%